Prospects For BigTech Ecosystems as Issuers of Global Stablecoins - Dmitry KOCHERGIN; Ekaterina SHESHUKOVA (Communications of International Proceedings, 2023)
The article is devoted to identifying promising areas for ecosystems in the payment sphere as providers of financial products (services) and issuers of global stablecoins. The research analyzed current approaches to the definition of ecosystems, proposed the author's interpretation, identified the main advantages associated with the participation of ecosystems in financial and payment intermediation, reviewed the models of provision of financial and payment services by ecosystems and identified the regulatory framework of their activities in foreign countries, marked out prospects of ecosystem activities in the payment sphere
Keywords: ecosystems; BigTechs; payment services; global stablecoins